Contingency between S & OP design and planning environment. Issue 8 (7th September 2015) - Ivert, Linea Kjellsdotter; Dukovska-Popovska, Iskra; Fredriksson, Anna; Dreyer, Heidi C.; Kaipia, Riikka
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to understand how companies design sales and operations planning (S & OP) contingent on the planning environment (PE). Design/methodology/approach – On the basis of the literature, the paper creates an analytical framework identifying the main constructs related to the PE and S & OP design, which is the basis for gathering and analysing qualitative data from eight cases in the food industry. The findings highlight the relations between S & OP and the PE, and are used for generating three propositions. Findings – Responding to the complex and uncertain PE, the companies set up S & OP on a stock-keeping unit (SKU) level, with the possibility of re-planning and a flexible planning horizon, thus differing from what has generally been suggested in the literature. In addition, the companies are aligning the inputs, activities, and outcomes of the S & OP process to the PE. Particularly important environmental contingencies are uncertainty connected to demand and supply, frequent product launches, and production network complexity. Product-related variables have a lower impact on the S & OP design. Research limitations/implications – The present study is limited to one industry only and a comparison between industries with larger data sets would be valuable in future studies. The study selected cases based on their S & OP maturity; further studies need to explore the effect of the alignment of S & OP and the PE on the planning performance. Originality/value – In the literature, S & OP is presented as a generic process with a strict formal design that is equal for all companies. The study provides insights into how companies adjust S & OP according to the PE.